Transtornos mentais comuns em trabalhadores : revisão sistemática da literatura - Busetti , Marcela Vargas (2015)
The Common Mental Disorders are defined as anxiety disorders, depression and somatoform and its high prevalence is related to the growth of psychological distress in labor organizations. This dissertation investigated through literature, the prevalence and factors associated with Common Mental Disorders workers. Article I, entitled "Prevalence and factors associated with Common Mental Disorders workers: a systematic review of the literature", aimed to determine the prevalence and factors associated with Common Mental Disorders in Brazilian workers. From this study it was possible to identify the prevalence of Common Mental Disorders for many professions in the years 2004 to 2013. The results show an important variation of prevalence ranging from 6.1% to 83.3%.The main associated factors were gender, income, diagnosis of illness and psychosocial aspects of work. Article II, called "Common Mental Disorders in women: a gender analysis" aimed to describe and analyze genetic, personality and social that can be related to the Common mental disorders in women. The reflections on the social determinants related to women's mental illness allows us to understand the context of these women to reflect on possible psychosocial interventions